Biomarkers for autoimmunie disease diagnosis in the public health sector: A systematic review and meta-analysis - Morar, Zeena (Department of Public Health and Family Medicine, 2025)
Rheumatic heart disease (RHD), rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) are autoimmune diseases with drastic effects on quality of life. Diagnostic challenges remain, especially given the prevalence of these diseases among people of low socioeconomic status. The purpose of this review was to determine, from published case-control and cross-sectional studies, whether selected protein biomarkers are discriminatory indicators of RHD, RA and SLE. This review was carried out in accordance with the Preferential Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). A significant increase in adiponectin was found in patients with SLE and in patients with RA (including those with severe and mild cases of RA) as compared with healthy controls. Ficolin-3 was significantly upregulated in SLE patients and downregulated in RHD patients, while alpha-2-glycoprotein 1 was significantly upregulated in SLE patients compared to controls. Gelsolin was significantly downregulated in patients with RHD and in SLE patients with a flare-up and in remission. Given that data remain scant, further research into these proteins, along with others not previously identified, is warranted to evaluate their discriminatory power for the development of a cost-effective point-of-care diagnostic test.